Kebijakan Publik dan Penataan Parkir Liar: Analisis Implementasi Perda Nomor 1 Tahun 2024 tentang Pajak dan Retribusi Daerah di Kota Gorontalo - Arsjad, Muh. Fachri; Sahi, Nirmala; Bilondatu, Nikma; Polapa, Lianti; Tabo, Sarfan; Nuna, Muten (Jurnal Publisitas, 2026)
The increasing number of motor vehicles in Gorontalo City has led to various transportation problems, one of which is the widespread practice of illegal parking that disrupts traffic flow and potentially reduces Regional Original Revenue (PAD). To address this issue, the Gorontalo City Government enacted Regional Regulation Number 1 of 2024 concerning Regional Taxes and Retributions as the legal basis for parking regulation and control. This study aims to analyze government policies and assess the effectiveness of the implementation of Regional Regulation Number 1 of 2024 in controlling illegal parking and increasing PAD in Gorontalo City. This research employs a qualitative approach with a descriptive method. Data were collected through observation, interviews with officials of the Transportation Agency and the community, as well as documentation. The results indicate that the policy on controlling illegal parking has been implemented through stages of problem identification, policy formulation, policy adoption, implementation, and evaluation. Policy implementation is carried out through the designation of official parking locations, field supervision, and guidance for parking attendants. However, the implementation still faces several constraints, including limited parking space, low public awareness, and inadequate security at parking locations. Overall, the implementation of Regional Regulation Number 1 of 2024 is considered relatively effective in reducing illegal parking practices, but it still requires strengthened supervision and continuous socialization to achieve optimal policy outcomes. Based on these findings, this study recommends that the Government of Gorontalo City increase the provision of adequate parking facilities, strengthen technology-based monitoring systems, and intensify public socialization for the community and parking attendants. In addition, cross-sectoral synergy and consistent enforcement of sanctions are needed to improve compliance with the regulation and optimize the contribution of the parking sector to Local Own-Source Revenue (PAD).